A prospective study of complications from comprehensive abortion care services in Nepal - Andersen, Kathryn (BioMed Central, 2012)
BACKGROUND: In March 2002, Nepal's Parliament approved legislation to permit abortion on request up to 12 weeks of pregnancy. Between 2004 and 2007, 176 comprehensive abortion care (CAC) service sites were established in Nepal, leading to a rise in safe, legal abortions. Though monitoring systems have been developed, reporting of complications has not always been complete or accurate. The purpose of this study was to report the frequency and type of abortion complications arising from CAC procedures in different types of facilities in Nepal. METHODS: A total of 7,386 CAC clients from a sample of facilities across Nepal were enrolled over a three-month period in 2008. Data collection included an initial health questionnaire at the time of abortion care and a follow-up questionnaire assessing complications, administered two weeks after the abortion procedure. A total of 7,007 women (95%) were successfully followed up. Complication rates were assessed overall and by facility type. Multivariable logistic regression was used to assess the association between experiencing a complication and client demographic and facility characteristics. RESULTS: Among the 7,007 clients who were successfully followed, only 1.87% (n = 131) experienced signs and symptoms of complications at the two-week follow up, the most common being retained products of conception (1.37%), suspected sepsis (0.39%), offensive discharge (0.51%) and moderate bleeding (0.26%). Women receiving care at non-governmental organization (NGO) facilities were less likely to experience complications than women at government facilities, adjusting for individual and facility characteristics (AOR = 0.18; 95% CI: 0.08-0.40). Compared to women receiving CAC at 4-5 weeks gestation, women at 10-12 weeks gestation were more likely to experience complications, adjusting for individual and facility characteristics (AOR = 4.21; 95% CI: 1.38-12.82). CONCLUSIONS: The abortion complication rate in Nepali CAC facilities is low and similar to other settings; however, significant differences in complication rates were observed by facility type and gestational age. Interventions such as supportive supervision to improve providers' uterine evacuation skills and investment in equipment for infection control may lower complication rates in government facilities. In addition, there should be increased focus on early pregnancy detection and access to CAC services early in pregnancy in order to prevent complications.